KEABSAHAN PUTUSAN ARBITRASE ONLINE DI INDONESIA - Ellen Valentina Santoso (Fakultas Hukum Universitas Kristen Indonesia, 2020)
Arbitration is a means of resolving a civil dispute outside a public trial based on an arbitration agreement made in writing by the disputing parties, in Indonesia the arbitration is governed by the Act Number 30 of year 1999 on arbitration and Alternative dispute resolution. In the implementation of the arbitration experienced a development that was initially only conventional to the direction of online arbitration that almost all the implementation of the arbitration from the start of the registration until the award is done by the Internet Network (online), But until now there no specific regulation that covered the online arbitration especially in the validity of online arbitration award that raises legal uncertainty.